APPLICATION OF NUTRIENT-PROTECTIVE SOLUTION IN THE ELECTRIC FIELD OF CORONA DISCHARGE AT THE FACILITY VEGETABLE - Inozemtsev, G.; Okushko, A. (Енергетика і автоматика, 2016)
Considered fundamentally new way of charging nourishing and protective solution during the application of an electric field on plant sites.